Correlation of gas exchange threshold and first muscle oxyhemoglobin inflection point with time-to-exhaustion during heavy-intensity exercise - Coquart, J. B.; Mucci, P.; L'hermette, M.; Chamari, K.; Tourny, C.; Garcin, M. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The twofold aim of the study was to: 1) compare the gas exchange threshold (GET), the first oxyhemoglobin inflection point ([O2Hb]-T), and perceptual threshold as determined during an incremental exercise test, and 2) investigate the link between each threshold and time-to-exhaustion during heavy intensity exercise.